An Efficient Synthesis of 2-Substituted Quinazolin-4(3H)-ones Catalyzed by Iron(III) Chloride - Mekala, Ramamohan; Akula, Raghunadh; Kamaraju, Raghavendra Rao; Bannoth, Chandrasekhar Kothapalli; Regati, Sridhar; Sarva, Jayaprakash (Synlett, 2014)
A simple and highly efficient synthesis of 2-substituted quinazolin-4(3H)-ones by the iron(III) chloride catalyzed reaction of isatoic anhydride with various amidoxime derivatives was developed. Several aryl and alkyl amidoximes were screened to demonstrate the scope of the methodology.
Keywords: heterocycles; polycycles; ketones; catalysis; iron; quinazolinones